Planetary nebulae and how to find them: A concise review - Parker , Quentin A. (Frontiers in Astronomy and Space Sciences, 2022)
This review provides useful background and information on how we find, vet and compile Planetary Nebulae (PNe) candidates and verify them. It presents a summary of the known Galactic PNe population and their curation in the Hong Kong/AAO/Strasbourg/Hα PNe catalogue, “HASH”. It is a simple introduction for anyone interested in working with PNe, including postgraduate students entering the field and for more general interest too.